Pharmacokinetics and pharmacodynamics of Ro 44–3888 after single ascending oral doses of sibrafiban, an oral platelet aggregation inhibitor, in healthy male volunteers - Wittke, Bärbel (Blackwell Science Inc, 1999)
AIMS: This study constituted the first administration of the oral platelet inhibitor, sibrafiban, to humans. The aim was to investigate the pharmacokinetics and pharmacodynamics of Ro 44–3888, the active principle of sibrafiban, after single ascending oral doses of sibrafiban. Particular emphasis was placed on intersubject variability of the pharmacokinetic and pharmacodynamic parameters of Ro 44–3888. METHODS: The study consisted of three parts. Part I was an open ascending-dose study to determine target effect ranges of sibrafiban. Part II, a double-blind, placebo-controlled, parallel-group study, addressed the intersubject variability of pharmacokinetic and pharmacodynamic parameters of the active principle at a sibrafiban dose achieving an intermediate effect. Part III was a double-blind, placebo-controlled, ascending-dose design covering the complete plasma concentration vs pharmacodynamic response curve of sibrafiban. RESULTS: At sibrafiban doses between 5 mg and 12 mg, the pharmacokinetics of free Ro 44–3888 in plasma were linear whereas those of total Ro 44–3888 were non-linear because of the saturable binding to the glycoprotein IIb-IIIa receptor. Saturation of the GP IIb–IIIa receptor was reached at plasma concentrations of 15.9 ng ml(−1). At sibrafiban doses up to 2 mg, ADP-induced platelet aggregation was inhibited by 50%, whereas the inhibition of TRAP-induced platelet aggregation was about 20–30%. At the higher doses, ADP-induced platelet aggregation was almost completely inhibited while a clear dose-response could be observed with TRAP-induced inhibition of platelet aggregation at sibrafiban doses of 5 to 12 mg. Ivy bleeding time increased very steeply with dose with a significant prolongation observed at doses of 5 to 7 mg of sibrafiban (5–7 min, >30 min in one case). At a sibrafiban dose of 12 mg, the stopping criterion for dose escalation (prolongation of the Ivy bleeding time >30 min in three out of four subjects per dose group) was reached. The interindividual coefficients of variation of the integrated pharmacokinetic and pharmacodynamic parameters (AUC and AUE) were below 20%, thus lying well within the pre-set level of acceptance. CONCLUSIONS: With a low intersubject variability of its pharmacokinetic and pharmacodynamic parameters, linear pharmacokinetics and pharmacodynamic effects closely related to its plasma concentrations, Ro 44–3888 has good pharmacological prerequisites for a well controllable therapy of secondary prevention of arterial thrombosis in patients with acute coronary syndrome.